2021
DOI: 10.1016/j.catena.2020.104951
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the compound effect of geomorphology, vegetation, and climate change on paleopedogenesis in sensitive environments (Northern Apennines, Italy)

Abstract: Complex sequences of paleosols are often formed by the interaction between pedogenesis and geomorphological evolution. Their study, particularly in mountain areas, is useful to reconstruct past environmental conditions as well as climate shifts, and to gather information on the morphodynamical processes affecting the landscape through time. Since the combined role that all different factors can play in the soil formation and evolution through time and space influences the formation and evolution of those compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Cusna geosite and surrounding area is the presence of a wide range and constantly updated data of different disciplines. The presence of abundant literature focused on pedology, geomorphology, archeology, climatic and vegetation characterization, and specific laboratory analyses, such as radiocarbon dating, anthracological, and dendrochronological studies, e.g., [26,[29][30][31]36] allowed for the creation of an innovative trail able to enhance the soil as a paleoenvironmental archive and as a meeting point for different disciplines. In literature, geotrails are always created starting from an accurate analysis of the geographical, geological, and geomorphological characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cusna geosite and surrounding area is the presence of a wide range and constantly updated data of different disciplines. The presence of abundant literature focused on pedology, geomorphology, archeology, climatic and vegetation characterization, and specific laboratory analyses, such as radiocarbon dating, anthracological, and dendrochronological studies, e.g., [26,[29][30][31]36] allowed for the creation of an innovative trail able to enhance the soil as a paleoenvironmental archive and as a meeting point for different disciplines. In literature, geotrails are always created starting from an accurate analysis of the geographical, geological, and geomorphological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, along the Mt. Cusna toposequence (i.e., "a sequence of related soils that differ, one from the other, primarily because of topography as a soil-formation factor", https://www.soils.org/publications/soils-glossary/, accessed on 15 April 2023) (Figure 2f-h) different buried soil units have been identified and classified as Luvisols (Alfisols), formed during two distinct stability phases attributed to the Sub-Boreal and the most recent Atlantic period, characterized by a well or moderately developed brunification with clay illuviation [36]. The slopes of Mt.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the moderate OI values of the Inceptisols (~189) could reflect their formation over relatively coarse-textured sediments (i.e., levees and crevasse splay deposits) under well drained conditions [8], which allowed the rapid oxidation of the OM. These HI and OI values of the Inceptisols indicated that the kerogen essentially derived from land plants deposited under predominantly oxic conditions (Type III) and from refractory OM (Type IV) (e.g., [69]). Although Vertisols and Histosols presented similar HI average values, Vertisols showed a wider range compared to Histosols.…”
Section: Composition Of the Paleosol-derived (And Sedimentary) Organic Mattermentioning
confidence: 98%